ResÄ±stor Value Checker KÄ±t for EducatÄ±onal Purpose - Hanapi, Z.; Nashir, I. M.; Hussain, M. A. M.; Isa, N. S.; Maâ€™arof, N. N. M. I. Maâ€™arof (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The use of technology in creating Teaching Aids (TA) for the Teaching and Learning (TL) process has a great impact on delivering knowledge and skills as well as expediting the learning process amongst students. Additionally, game-based TA plays an important role in improving the achievement and efficiency of students in the classroom. This research was conducted to develop the education kit for TL Resistor Color Code (RCC). The main purpose of this education kit development is to help students understand the RCC through a fun learning environment based on hands-on learning activity. This education kit known as Resistor Value Checker (RVC) kit is built on the concept of 21st Century Learning (21-CL) which concerns about the use of appropriate technology in the process of the TL in the classroom. It is designed with the latest facilities and different from existing products in the market.Ã‚Â